answersLogoWhite

0


Best Answer

a = 3a + 4

0 = 2a + 4

2a = -4

a = -2

User Avatar

Wiki User

โˆ™ 2011-01-08 12:37:18
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.75
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1005 Reviews
More answers
User Avatar

sierrabock

Lvl 2
โˆ™ 2021-08-06 01:11:22

11

This answer is:
User Avatar
User Avatar

Haylie Prohaska

Lvl 1
โˆ™ 2021-08-08 20:05:44
great answer tyy!

Add your answer:

Earn +20 pts
Q: What is the solution to a equals 3a plus 4?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

Simplify 2a plus 3a plus 4 equals?

2a + 3a + 4 = 5a + 4


What is the answer to 3a plus 4?

3a plus 4 equals 3a +4. You can not combine the two parts because they are not like terms so there is no way to simplify this.


If 6a plus 3b equals 2 and b 4 then what is the value of 3a?

The solution for the value of 3a would be -3. The equation would be 6a + 3(4) = 2.


What is 4a plus 3a-4 equals 10?

4a+3a-4 = 10 4a+3a = 10+4 7a = 14 a = 2


What is the answer for 3a plus 13 equals 5a plus 5?

a is equal to 4


What is the solution to 5a plus 11 plus 3a - 7 equals -4?

So we have 5a + 11 + 3a - 7 = -4 Start by combining common terms such as the 5a and 3a to give you 8a and 11 and -7 to give you 4. So now your equation is 8a + 4 = -4. Subtract 4 from both sides gives you 8a = -8. Divide -8 by 8 to give you a = -1, your solution.


What is 3a plus 2 equals a-6?

It's a simple linear equation with 'a' as the variable.Here's how to find the solution:3a + 2 = a - 6Subtract '2' from each side of the equation:3a = a - 8Subtract 'a' from each side:2a = -8Divide each side by '2' :a = -4


How do you solve 3a plus 4 equals 4a-3?

3a + 4 = 4a - 3 4 = a -3 (subtract 3a from each side) 7 = a (add 3 to both sides) a = 7


What is 3a plus 2 plus 3a plus 2?

It is 6a + 4


What is the answer for 4y-4 plus 3a plus 7-6a-4?

4y - 4 + 3a + 7 - 6a - 4 = 4y -1 - 3a


What is the solution of 4 plus 2x equals 4?

x = 0


What is the solution of a 5a-5 equals 7 plus 2a?

5a - 5 = 7 + 2a ( subtract 2a from both sides) 3a - 5 = 7 (add 5 to both sides) 3a = 12 ( divide both sides by 3) a = 4

People also asked